2022
DOI: 10.1007/s44245-022-00006-z
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the mechanical behaviour of sandwich composite structures with circular honeycomb bamboo core

Abstract: Sandwich panels made with a bamboo core of different dimensions, packing geometries and facing materials are subjected to three-point bending tests and assessed through statistical and failure analysis. In addition to promoting a circular economy, this architecture holds great promise for replacing secondary structural components in sustainable construction and transportation facilities. The statistical analysis responses are associated with the equivalent density of the panels, flexural strength and modulus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…de Oliveira [22] used three-point bending tests to evaluate sandwich panels with a bamboo core with varying dimensions, packing geometries, and facing materials. Comparing the mechanical performance of the proposed sandwich panels to commercially available similar structures, which are often employed in the automotive and aerospace sectors, is impressive and competitive.…”
Section: Introductionmentioning
confidence: 99%
“…de Oliveira [22] used three-point bending tests to evaluate sandwich panels with a bamboo core with varying dimensions, packing geometries, and facing materials. Comparing the mechanical performance of the proposed sandwich panels to commercially available similar structures, which are often employed in the automotive and aerospace sectors, is impressive and competitive.…”
Section: Introductionmentioning
confidence: 99%
“…A simple and efficient two-step method has been invented to convert natural bamboo into a lightweight structural material exhibiting a superior strength and toughness due to its bamboo-like gradient laminated structure [ 36 ]. Statistical analysis and three-point bending tests of sandwich panels consisting of a bamboo core with different dimensions, packing geometry (cubic or hexagonal), and facing materials (aluminum or glass fiber-reinforced polymers) showed a dependence of the mechanical behavior on the shear strength and elastic modulus of the bamboo core and the flexural strength of the panels [ 37 ]. An appraisal of the mechanical properties and failure modes of laminated bamboo lumber has indicated that this material is a promising alternative to conventional building materials [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The significance of damage detection spans various composite materials, including laminate composites, sandwich composites, and composite joints, with applications ranging from aircraft and automotive to wind turbine blades (Yuan et al. , 2021; de Oliveira et al. , 2022; Soleymani et al ., 2021; Saeedifar and Zarouchas, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/1757-9864.htm ranging from aircraft and automotive to wind turbine blades (Yuan et al, 2021;de Oliveira et al, 2022;Soleymani et al, 2021;Saeedifar and Zarouchas, 2020). Within the domain of composite materials, numerous damage detection methods have been explored, encompassing sensor measurement techniques such as piezoelectric and strain gauge sensors, as well as methods like acoustic emission and electric resistance (Kong et al, 2023;Wang et al, 2019;Zamani et al, 2019;Zamani et al, 2016;Sha et al, 2019).…”
mentioning
confidence: 99%